Biopartitioning Micellar Chromatography Determination of Nucleosides and Bases in Bailing Capsule - Li, Cheng-Ping; Xu, Lin (Asian Journal of Chemistry, 2013)
In this work, we reported the determination of contents of three nucleosides (uridine, guanosine and adenosine) and two bases (uracil and adenine) in bailing capsule by biopartitioning micellar chromatography. The analytes were carried out on a Sepax-C18 (4.6 mm × 250 mm, 5 μm) and mobile phase consisted of 0.02 mol L-1 polyoxyethylene (23) lauryl ether (Brij35), 0.02 mol L-1 sodium dihydrogen phosphate-disodium hydrogen phosphate (pH = 7.4) and 9.2 g L-1 NaCl. The flow rate was 0.6 mL min-1, the detection wavelength and column temperature were set up at 260 nm and 37 ºC, respectively. Uridine, guanosine, adenosine, uracil and adenine could be completely separated from each other and had good linerarity. The method is simple, sensitive,accurate, stable with a better reproducibility. So, it can assess and control the quality of preparations of fermental cordyeps-bailing capsule comprehensively.